DILEMA MORAL MAHASISWI BERAGAMA ISLAM SEBAGAI PENIKMAT SERIAL BOYS’ LOVE DARI THAILAND - Yunika, Nanda; Alimi, Moh. Yasir (Al-Amien Prenduan University, Sumenep, 2025)
The popularity of the Boys' Love (BL) series from Thailand has reached a global audience including Muslim women. This raises a moral dilemma felt by Muslim women due to their dual identity. The dual identity includes identity as a Muslim woman and identity as a connoisseur of the Boys' Love (BL) series from Thailand. The moral dilemma that occurs is certainly very related to the contradiction between their norms and preferences. The purpose of this study is to explore in depth the moral dilemma and also the effort to overcome the perceived moral dilemma and analyze the reasons and viewing behaviors shown for the preference as connoisseurs of the BL Thai series in Muslim female students at one of the public universities in Semarang. This study uses a descriptive qualitative method with data collection techniques through observation and in-depth interviews. The results of the study show that: (1) The reasons why Muslim female students consume the Thai BL series are different from each other. (2) The behavior of Muslim female students watching the BL Thailand series is shown through the frequency of consumption of the BL Thai series to their interaction with the community. (3) There is an impact felt by Muslim female students as a result of enjoying the BL Thailand series. (4) The moral dilemma felt was guilt due to enjoying the BL Thailand series. (5) There are two efforts made to overcome moral dilemmas, namely by responding to the moral dilemma or avoiding the perceived moral dilemma.